De negro a pardo: memória, identidade e invisibilidade, na Escola Bom Pastor, Ipixuna do Pará - GUEDES, Odaléia Maria Barbosa (2018)
This article aims to reflect on an intriguing school phenomenon: the denial of black identity by the students of the State School for Infant and Elementary Education “Bom Pastor”, located in the District of Canaã, in the municipality of Ipixuna do Pará (Brazil). We will discuss the efforts of the portuguese colonization and the brazilian State to make invisible the identity of the black people, as well as the consequences of the invisibility of the black in the curriculum and didactic materials, as well as its implications in the construction of the black identity of the students of that school. In addition, we point out the importance of black self-identification, its memory and culture, because these are fundamental elements in the construction of the identity of a multicultural and multiethnic nation like Brazil. In this perspective, the decolonization of the School Curriculum is of paramount importance, so that it can assure a more egalitarian education, and at the same time, it seeks the promotion of ethno-racial equity. The school is a space for fomenting the foundations of democracy and where different peoples of multiple identities circulate; it is also a place of various conflicts, since most of the times it does not value the ethnic plurality existing in it, and generally the values of the hegemonic groups are imposed to the detriment of the other ethnic groups.